Part III: Artwork (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2022)
I enjoy the challenge of using scraps from other people’s projects or donated fabric to create something functional and beautiful. In this case I was given someone’s ‘extra’ nine-patch blocks and then created additional nine-patch and hour-glass blocks which are used alternately in rows. Most of my quilts are donated to organizations that provide them to families in need.